2018
DOI: 10.1177/1942775118819661
|View full text |Cite
|
Sign up to set email alerts
|

What Makes a Leadership Preparation Program Exemplary?

Abstract: What makes a leadership preparation program exemplary? All three exemplary programs featured in this special issue evidence strong learning orientations and more sustained improvement work in their pursuit of exemplary preparation. I therefore examine exemplary preparation from a process perspective that emphasizes continuous improvement. To help readers make more meaning of the exemplary preparation programs featured in this special issue as well as to advance the field's understanding of and ability to suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 32 publications
0
21
0
2
Order By: Relevance
“…In program development and design, Cosner (2019) suggests starting with a problem of practice and engaging those with experience in the problem in developing solutions for it. In a similar way, the team of university and educational partners commenced the study by considering how to effectively support the professional learning of school principals in relationship to leading inclusive schools for students with SEN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In program development and design, Cosner (2019) suggests starting with a problem of practice and engaging those with experience in the problem in developing solutions for it. In a similar way, the team of university and educational partners commenced the study by considering how to effectively support the professional learning of school principals in relationship to leading inclusive schools for students with SEN.…”
Section: Discussionmentioning
confidence: 99%
“…Authenticity. First, web-based case studies need to be developed which authentically represent problems of practice (Cosner, 2019;Wang et al, 2018). The participants in this study noted that one of the defining aspects of the case studies was that they were based on actual events and authentically reflected their lived experiences.…”
Section: Five Lessons For Developing Web-based Case Studiesmentioning
confidence: 99%
“…Such pathways are cost-effective (Kaufman et al, 2017) and produce leaders better prepared for high-need schools (Darling-Hammond et al, 2007; Huang et al, 2012). Methodological challenges aside (Grissom et al, 2019), a growing research base has shown that the design of these programs matters (Cosner, 2019; Crow & Whiteman, 2016; Darling-Hammond et al, 2007; Davis & Darling-Hammond, 2012; Young, 2015). As a framework for what makes principal preparation exemplary, the Darling-Hammond et al (2007) study is frequently cited (Cosner, 2019).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Methodological challenges aside (Grissom et al, 2019), a growing research base has shown that the design of these programs matters (Cosner, 2019; Crow & Whiteman, 2016; Darling-Hammond et al, 2007; Davis & Darling-Hammond, 2012; Young, 2015). As a framework for what makes principal preparation exemplary, the Darling-Hammond et al (2007) study is frequently cited (Cosner, 2019). Examining eight different university-based programs, they found that rigorous recruitment and selection, research-based content, curricular coherence, field-based internships, problem-based learning strategies, cohort structures, mentoring or coaching, and collaboration between universities and school districts were important considerations.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The importance of this Special Issue’s focus is amplified by the dearth of existing literature that attends to pedagogical approaches in educational leadership (Byrne-Jimenez et al, 2017). Although there is both a need and growing appetite for attention to program improvement (Cosner, 2019; Cunningham et al, 2019; Young & Eddy-Spicer, 2019), there are relatively few granular accountings about pedagogical considerations and development processes or the resultant learning designs to provide insights for interested designers throughout the field.…”
mentioning
confidence: 99%